超音波診断システムおよび超音波診断装置 (2012)
超音波探触子（１１）は、少なくとも１方向に配列された超音波変換素子群よりなる。ビームフォーミング部（９１）は、被検体内部の走査線群に沿って存在するサンプル点列に超音波をフォーカスし、かつ各超音波変換素子の送受信信号にディレイ及びアポダイズを掛けることにより走査線群と実質的に直交する方向に変調された音場感度を形成する。検出部（９０）は、相異なる時点での各サンプル点における受信信号間の演算によって、サンプル点に於ける走査線群に接する方向の変位、及び走査線に実質的に直交する曲線群に接する方向の変位を検出する。走査線群に実質的に直交する曲線群は、被検体内部において超音波探触子（１１）に対して固定された２点からの超音波パルスの到達時間の和が実質的に同一である点列からなる曲線の群である。 An ultrasonic probe (11) is constituted by a group of ultrasonic transducer elements arranged in at least one direction. A beam forming unit (91) forms acoustic field sensitivity modulated in a direction substantially orthogonal to a group of scan lines in a subject by focusing an ultrasonic wave on a sequence of sampling points existing along the group of scan lines, and applying delay and apodization on a transmission/reception signal of each of the ultrasonic transducer elements. A detecting unit (90) detects displacements at each of the sampling points in a direction tangential to the group of scan lines and in a direction tangential to a group of curves substantially orthogonal to the scan lines by arithmetic between reception signals for the sampling point at different time points. The group of curves substantially orthogonal to the group of scan lines is a group of curves in the subject, each of the curves being constituted by a sequence of points for which a total of times taken for ultrasonic pulses to reach from two points fixed to the ultrasonic probe (11) is substantially the same.